Comparison of host inflammatory responses between calcium-silicate base material and IRM - Chi-Jr Hung; Chia-Tze Kao; Ming-Yuo Shie; Tsui-Hsien Huang (Elsevier, 2014)
Background/purpose: The use of root-end filling materials designed to stimulate tissue repair in periradicular tissues is highly recommended. These materials should be proved good tissue compatibility. The aim of this study was to estimate the responses of Intermediate restorative material (IRM), mineral trioxide aggregate (MTA), and calcium silicate (CS) cement after implantation into a rat subcutaneous, including the immune response, and materials degradation. Materials and methods: Materials with the same chemical component were inserted into the bilateral pockets in each rat. Hematoxylin and eosin (H&E) staining was used to evaluate the immune response of tissue after implantation. Western blot was employed to quantify the COX-2 expression of tissue. Results: After implantation for 6 weeks, H&E staining showed that the inflamed fibrous capsule surrounding MTA and CS was thicker and looser. At 12 weeks, the tissue responses became very uniform for MTA and CS. The capsule was almost free of inflammatory cells and filled with fibroblasts. A significant increase in the thickness of fibrous tissue was observed after 3 weeks, 6 weeks, and 12 weeks for IRM at the respective time points (P < 0.05). Significant increases of 3.45-fold, 2.81-fold, and 2.78-fold in COX-2 synthesis were observed using IRM, as compared with the control, at 3 weeks, 6 weeks, and 12 weeks, respectively (P < 0.05). However, CS cement was found to reduce an inflammatory reaction compared to MTA at all time points (P < 0.05). Conclusion: These three cements could be considered to be biocompatible even though they induced different inflammatory responses and tissue changes during implantation tests in rats. CS cement did not induce acute inflammation and tissue responses similar to those reported for MTA.